Diseño del sistema de agua potable para los sectores Sintaguzo, Troje, Luceropamba y Chiniguaico de la comunidad los Galtes, parroquia Palmira, cantón Guamote, mediante la aplicación del software Epanet - Hidalgo Gavidia, Mario Esteban (2016)
The present project entitled "DISEÑO DEL SISTEMA DE AGUA POTABLE PARA LOS SECTORES SINTAGUZO, TROJE, LUCEROPAMBA Y CHINIGUAICO DE LA COMUNIDAD LOS GALTES, PARROQUIA PALMIRA, CANTÓN GUAMOTE, MEDIANTE LA APLICACIÓN DEL SOFTWARE EPANET", was developed with the aim of providing to the community concerned with the studies for the construction of a potable water system, so that they have an efficient, reliable, and technically designed system that complying with the parameters and current technical and environmental specifications. The basic services available at Los Galtes community do not allow them to have a high quality living conditions due to the lack of infrastructure in terms of drinking water. The project developed, provides service to 97 families with housing projection of 6-members per family, therefore the studied area has a total initial population of 582 inhabitants, the lifetime of the system was designed for 20 years, taking thus a final population of 724 beneficiaries. With the contribution of the Environmental Impact Study, it is concluded that there is not a high negative impact, since the construction of the required infrastructure does not affect the flora neither the fauna of the ecosystem. The project ends with budgeting, technical specifications and the work timetable for building the system.